Betrayal at Blackthorn Park - Kelly, Julia, 1986- (Kelly, Julia, 1986- Evelyne Redfern mystery, 2024)
"With mystery, intrigue, and the hints of romance international bestselling author Julia Kelly is known for, Evelyne Redfern returns in Betrayal at Blackthorn Park. Freshly graduated from a rigorous training program in all things spy craft, former typist Evelyne Redfern is eager for her first assignment as a field agent helping Britain win the war. However, when she learns her first task is performing a simple security test at Blackthorn Park, a requisitioned manor house in the sleepy Sussex countryside, she can't help her initial disappointment. Making matters worse, her handler is to be David Poole, a fellow agent who manages to be both strait-laced and dashing in annoyingly equal measure. However, Evelyne soon realizes that Blackthorn Park is more than meets the eye, and an upcoming visit from Winston Churchill means that security at the secret weapons research and development facility is of the utmost importance. When Evelyne discovers Blackthorn Park's chief engineer dead in his office, her simple assignment becomes more complicated. Evelyne must use all of her-and David's-detection skills to root out who is responsible and uncover layers of deception that could change the course of the war"--